Gregory's Shadow - Freeman, Don 1908-1978. (New York : Viking, 2000)
Gregory Groundhog and his shadow desperately look for each other after they become separated from one another just before their annual appearance on Groundhog Day.
Keywords: Woodchuck -- Fiction; Groundhog Day -- Fiction; Shadows -- Fiction